Analisis Kandungan Total Coliform pada Air Galon dan Higiene Sanitasi Perorangan Operator Depot Air Minum Isi Ulang (Studi Kasus: Kecamatan Koto Tangah, Kota Padang) - Nadya Khairannisa Andrizal; Rinda Andhita Regia; Shinta Silvia (Universitas Batanghari Jambi, 2019)
This study aims to analyze Total Coliform and its correlations with DAMIU sanitation hygiene in Koto Tangah District, Padang City. The study was conducted by sampling and questionnaires. Samples were obtained from 10 DAMIU consisting of raw water in the reservoir and the production water then carried out in duplicate. Interviews were conducted using questionnaires to DAMIU operators and observations to observe the sanitation of DAMIU. The analytical method used to determine the amount of Total Coliform is the MPN method. The type of question in the questionnaire is the close ended question with the Guttman scale. The results showed that Total Coliform in raw water ranged from 12-64 MPN / 100 ml and production water ranged from 6.2-15 MPN / 100 ml that it did not meet the quality standard limit based on Permenkes 492/2010, which was 0 MPN / 100 ml. After the complementary test, it is known that 50% of raw water samples and 20% of processed water are positive for E. coli bacteria. The results of the questionnaire showed that the personal hygiene on the DAMIU operators were 6.6% at